Head Pull-Through strength of pneumatically driven steel pins in wood structural panel sheathing. (15th November 2022) - Fung, Joyce; Whitworth, Cristina; Nolan, David; Jessee, Spencer; Serrette, Reynaud
Highlights: Fastener head pull-through strength model for nails and steel pins in wood- structural panels. Head bearing evaluated using experimental data from rod push-through strength. Steel pin knurl pattern included in model. Strength prediction agrees reasonably well with manufacturer data. Abstract: Wood structural panels may be attached to cold-formed steel framing with screws, pins, or staples. When subjected to uplift loads, induced fastener tension may result in connection failure due to pull-out from the steel framing or fastener head pull through the wood structural panel. For steel pins, no codified design provisions exist for the pin pull-through limit state in CFS construction. In earlier published work, an equation that accounted for pin head bearing and shank shear friction was proposed to estimate pull-through strength. In the study reported here, 102 rod punch-through tests were conducted to investigate head bearing strength of pins in wood structural panels, and manufacturer data was reviewed to propose adjustments for knurl pattern. Based on the data, a previously proposed equation was revised/updated. Predictions based on the revised equation were compared to test data and the comparison showed that the revised equation gave reasonably reliable strength estimates.